The Effect of Polymer Blend on the Third Order Nonlinearity of Oxazine Dye Doped Films by Using Z-Scan Techniques. - Jaffar, Amal F (Al-Nahrain Journal of Science, 2018)
The nonlinear optical properties of the laser dye Oxazine doped with polystyrene (OX /PS), Ox/poly methylmethacrylate (PMMA) and Ox/PS-PMMA blend films have been studded. The films deposited by free-casting technique and characterized by Z- scan technique .Z-scan experiment was performed using continuous wave (CW) diode laser at 650 nm at in two parts. The first part was done using a closed-aperture placed in front of the detector to measure the nonlinear refractive index ,with the second part; the aperture in front the detector was removed (open aperture) to measure the nonlinear absorption coefficient. The open-aperture curve exhibits a normalized transmittance (valley), indicating the presence of induced absorption. The observed nonlinearity is found to be of the third order, as it fits to two photon absorption process (TPA). The closed-aperture curve exhibits a peak to valley shape, indicating a negative value of the nonlinear refractive index n2. The effective values of the nonlinear refractive index n2, the nonlinear absorption coefficient β2, real and imaginary parts of the third-order optical nonlinearity, χ(3) for Ox/PMMA-PS films comparatively with that of Ox/PMMA and Ox/PS has much lower transmittance value obtained shows that these films can be used as efficient optical limiters.